2020
DOI: 10.1111/1477-9552.12368
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Mistaken Identity? Measuring Rates of Improved Seed Adoption in Tanzania Using DNA Fingerprinting

Abstract: Studies of improved seed adoption in developing countries are almost always based on household surveys and are premised on the assumption that farmers can accurately self-report their use of improved seed varieties. However, recent studies suggest that farmers' reports of seed varieties planted, or even whether the seed is local or improved, are sometimes inconsistent with the DNA fingerprinting results of those crops. We use household survey data from Tanzania to test the alignment between farmer-reported and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…Corresponding assessment of returns on investment may be inaccurate, and decisions on future actions by policy makers and investors are adversely affected. Numerous tools relying on a small number of genetic markers to identify genetically homogenous inbred crop lines and clonal horticultural varieties have been developed, and the extent of seed misidentification in crops is increasingly recognized in agriculture through the application of these methods (Rabbi et al, 2015 ; Chen et al, 2016 ; Floro et al, 2018 ; Kosmowski et al, 2019 ; Wineman et al, 2020 ). However, the development of comparable tools to distinguish between strains of outcrossing aquaculture species is challenging, and information on the extent of misidentification of tilapia strains is currently limited (Baggio et al, 2016 ; Oponda et al, 2017 ; Ordoñez et al, 2017 ; Moses et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding assessment of returns on investment may be inaccurate, and decisions on future actions by policy makers and investors are adversely affected. Numerous tools relying on a small number of genetic markers to identify genetically homogenous inbred crop lines and clonal horticultural varieties have been developed, and the extent of seed misidentification in crops is increasingly recognized in agriculture through the application of these methods (Rabbi et al, 2015 ; Chen et al, 2016 ; Floro et al, 2018 ; Kosmowski et al, 2019 ; Wineman et al, 2020 ). However, the development of comparable tools to distinguish between strains of outcrossing aquaculture species is challenging, and information on the extent of misidentification of tilapia strains is currently limited (Baggio et al, 2016 ; Oponda et al, 2017 ; Ordoñez et al, 2017 ; Moses et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Again, intercropping initially appears to be detrimental to rice yield (columns 1-2) in a statistically significant manner until we account for the space taken up by other crops. Surprisingly, the use of improved rice seed is not statistically significantly associated with yield, although Wineman et al (2019) suggest that farmers' identification of improved varieties may not always be correct.…”
Section: Econometric Resultsmentioning
confidence: 88%
“…Error type I and Error type II are calculated based on the genotyping identification and the farmer naming of varieties. Those errors commonly occur in these types of studies as reported by Wineman et al (2020)…”
Section: Varietal Identification By Dna Fingerprintingmentioning
confidence: 97%